Radical politics in Hong Kong: Can business make a difference? - TANG, James T. H. (Institutional Knowledge at Singapore Management University, 2009)
As Hong Kong in 2009 retained its title as the world’s freest economy for the fifteenth consecutive year, radicalism seemed to have gained wider support in local politics at a time of economic turbulence—even though a timetable for universal suffrage has been set.